New Insights into Autoinducer-2 Signaling as a Virulence Regulator in a Mouse Model of Pneumonic Plague - Eric C. Fitts (American Society for Microbiology, 2016)
ABSTRACT The Enterobacteriaceae family members, including the infamous Yersinia pestis, the causative agent of plague, have a highly conserved interbacterial signaling system that is mediated by the autoinducer-2 (AI-2) quorum-sensing molecule. The AI-2 system is implicated in regulating various bacterial virulence genes in diverse environmental niches. Deletion of the gene encoding the synthetic enzyme for the AI-2 substrate, luxS, leads to either no significant change or, paradoxically, an increase in in vivo bacterial virulence. We showed that deletion of the rbsA and lsrA genes, components of ABC transport systems that interact with AI-2, synergistically disrupted AI-2 signaling patterns and resulted in a more-than-50-fold decrease in Y. pestis strain CO92 virulence in a stringent pneumonic plague mouse model. Deletion of luxS or lsrK (encoding AI-2 kinase) from the ΔrbsA ΔlsrA background strain or complementation of the ΔrbsA ΔlsrA mutant with the corresponding gene(s) reverted the virulence phenotype to that of the wild-type Y. pestis CO92. Furthermore, the administration of synthetic AI-2 in mice infected with the ΔrbsA ΔlsrA ΔluxS mutant strain attenuated this triple mutant to a virulence phenotype similar to that of the ΔrbsA ΔlsrA strain in a pneumonic plague model. Conversely, the administration of AI-2 to mice infected with the ΔrbsA ΔlsrA ΔluxS ΔlsrK mutant did not rescue animals from lethality, indicating the importance of the AI-2–LsrK axis in regulating bacterial virulence. By performing high-throughput RNA sequencing, the potential role of some AI-2-signaling-regulated genes that modulated bacterial virulence was determined. We anticipate that the characterization of AI-2 signaling in Y. pestis will lead to reexamination of AI-2 systems in other pathogens and that AI-2 signaling may represent a broad-spectrum therapeutic target to combat antibiotic-resistant bacteria, which represent a global crisis of the 21st century. IMPORTANCE Yersinia pestis is the bacterial agent that causes the highly fatal disease plague. The organism represents a significant concern because of its potential use as a bioterror agent, beyond the several thousand naturally occurring human infection cases occurring globally each year. While there has been development of effective antibiotics, the narrow therapeutic window and challenges posed by the existence of antibiotic-resistant strains represent serious concerns. We sought to identify novel virulence factors that could potentially be incorporated into an attenuated vaccine platform or be targeted by novel therapeutics. We show here that a highly conserved quorum-sensing system, autoinducer-2, significantly affected the virulence of Y. pestis in a mouse model of pneumonic plague. We also identified steps in autoinducer-2 signaling which had confounded previous studies and demonstrated the potential for intervention in the virulence mechanism(s) of autoinducer-2. Our findings may have an impact on bacterial pathogenesis research in many other organisms and could result in identifying potential broad-spectrum therapeutic targets to combat antibiotic-resistant bacteria, which represent a global crisis of the 21st century.